Entrepreneurial skills according to principles of entrepreneurial education among chemistry department students at the faculty of education for pure sciences, Ibn Al-Haytham - Hussain, Hawraa Oudah; Ahmed, Basma Mohammed; Hatim, Khalid Hussein (Edelweiss Applied Science and Technology, 2025)
The aim of the current research is to identify the degree of availability of entrepreneurial skills according to the principles of entrepreneurial education among the students of the Chemistry Department at the Faculty of Education for Pure Sciences, Ibn Al-Haytham. The research adopted a descriptive research approach, and the sample consisted of 100 male and female students from the fourth-year Chemistry Department for the academic year 2024–2025, both in the morning and evening sessions, representing 75% of the community, selected randomly. The research tool was an entrepreneurial skills scale based on the principles of entrepreneurial education, consisting of 30 items distributed across six skill areas: personal skills, thinking skills, technological and technical skills, social skills, practical skills, and administrative skills. Using the Statistical Package for the Social Sciences (SPSS-22), the results showed that entrepreneurial skills based on entrepreneurial education principles are available among the Chemistry Department students at the Faculty of Education for Pure Sciences, Ibn Al-Haytham. The research recommended several suggestions, including renewing the role of universities to transform into entrepreneurial universities capable of equipping students with the knowledge and skills necessary to become entrepreneurs capable of meeting the ever-evolving demands of the labor market. Additionally, it recommended training teaching staff on how to adopt and promote entrepreneurial thinking and education principles, thus enhancing entrepreneurial skills among students. The research also suggested further studies on the impact of academic programs in universities on acquiring entrepreneurial skills among students.